Pengaruh Terapi Relaksasi Benson terhadap Tingkat Nyeri Pasien Post Operasi Benign Prostatic Hyperplasia di RSUD Dr. H. Slamet Martodirdjo - Kanesya Nurussifa Maulidina; Aisyah Nur Azizah; Istiqomah Rosidah (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Benign Prostatic Hyperplasia (BPH) is a benign enlargement of the prostate gland. One of the treatments for BPH is surgery. Any surgical procedure can cause pain due to the surgical incision. Pain management can be achieved through non-pharmacological therapies, one of which is Benson relaxation therapy. Benson relaxation is an adaptation of deep breathing techniques that involves the patient’s belief. To determine the effect of Benson relaxation therapy on pain levels in patients following Benign Prostatic Hyperplasia (BPH) surgery at Dr. H. Slamet Martodirdjo General Hospital. The study design used in this research was a quasi-experimental study with a one-group pre-test post-test design. The statistical test used in this study was the Wilcoxon Signed Rank Test. The sample size in this study was 37 respondents selected using purposive sampling. Pain was measured using the Number Rating Scale (NRS). The results of the study showed that the average pain scale before the Benson relaxation therapy intervention was 4.78, and after the Benson relaxation therapy intervention, the average pain scale decreased to 2.97. The statistical test yielded a p-value of 0.000 < 0.05. Benson relaxation therapy has an effect on the pain scale in patients who have undergone surgery for Benign Prostatic Hyperplasia (BPH) at Dr. H. Slamet Martodirdjo Regional General Hospital.